Implementation of virtual reality technology to decrease patients' pain and nervousness during colonoscopies: a prospective randomised controlled single-blinded trial. Issue 3 (2022) - Liu, Qizhi; Zang, Yunhua; Zang, Wei; Cai, Wenpeng; Li, Weiwei; Guo, E Ya'nan; Xin, Cheng; Tu, Xiaohuang
No abstract available